Strengths and Weaknesses of Self-Regulated Learning through YouTube: Indonesian EFL Students’ Perceptions - Hj. Fadhilah Harahab Putri; Agus Wijayanto; Slamet Supriyadi (ELS Journal on Interdisciplinary Studies in Humanities, 2020)
The recent advancements in technology are growing rapidly, because of that the demands of Internet are increasing rapidly. Include the use of website and application. Technology has brought various potentials for language learning. Therefore, in this research the aims are to determine the perceptions of EFL students and the strengths and weaknesses of self-regulated learning using YouTube. To achieve the objective of the research, the method used in this research is a case study. The data in this research were collected through in-depth interviews. The subjects in this research were four undergraduate students who are majoring in English education from university in Indonesia and they were purposively selected, so that they can provide sufficient information. The results in this research showed the positive perceptions of students towards EFL students self-regulated learning using YouTube. They declared that the use of YouTube could facilitate them in regulating their learning English, brings joy, pleasure and excitement during the learning process. In addition, in this research found out that the strengths of self-regulated learning using YouTube; YouTube provides a lot of learning materials, the ease to use YouTube, flexibility of time and place when using YouTube in regulating their learning. Meanwhile the weaknesses are financial constraints and problem of Internet connectivity.